2019
DOI: 10.5888/pcd16.180594
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Relative Impact of Clinical and Preventive Community-Based Interventions: An Example Based on the Community Transformation Grant Program

Abstract: Introduction Public health focuses on a range of evidence-based approaches for addressing chronic conditions, from individual-level clinical interventions to broader changes in policies and environments that protect people’s health and make healthy living easier. This study examined the potential long-term impact of clinical and community interventions as they were implemented by Community Transformation Grant (CTG) program awardees. Methods We used the Prevention Impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Given the important role that differential risk plays in the CV health of women from racial/ethnic minority backgrounds [20,[116][117][118][119], we recommend developing clinical, community, and virtual interventions to target risk factors in this group. These types of initiatives have proven effectiveness with respect to mortality and cost reduction [133]. While lifestyle and community interventions related to reducing the burden of type 2 DM [91][92][93][94], hypertension [134], and obesity [135] have been shown to be effective in women from racial/ethnic minority backgrounds, widespread incorporation of such initiatives is lacking [17].…”
Section: Cardiac Care For Women Beyond 2020mentioning
confidence: 99%
“…Given the important role that differential risk plays in the CV health of women from racial/ethnic minority backgrounds [20,[116][117][118][119], we recommend developing clinical, community, and virtual interventions to target risk factors in this group. These types of initiatives have proven effectiveness with respect to mortality and cost reduction [133]. While lifestyle and community interventions related to reducing the burden of type 2 DM [91][92][93][94], hypertension [134], and obesity [135] have been shown to be effective in women from racial/ethnic minority backgrounds, widespread incorporation of such initiatives is lacking [17].…”
Section: Cardiac Care For Women Beyond 2020mentioning
confidence: 99%
“…We examined the articles involving upstream prevention measures in detail. Among them, lifestyle approaches (balanced diet, moderate exercise, tobacco control, and mental health) were the most simulated prevention measures (n = 15, 44.1%) ( 9 – 12 , 19 29 ). Through simulation, the researchers found that lifestyle modification can reduce the incidence of chronic diseases, premature death, and medical costs among people with chronic disease, but the effect of lifestyle simulation prevention measures was more powerful in the long term ( 19 21 , 23 – 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Downstream prevention consists of clinical treatment and care of people with chronic diseases (n = 19 articles [55.9%]) ( 9 , 10 , 13 15 , 17 , 18 , 23 , 24 , 26 , 27 , 29 , 31 , 33 , 34 , 36 39 ). Some studies found that clinical treatment and care of people with chronic diseases could significantly reduce mortality.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Prevention Impacts Simulation Model (PRISM), developed by CDC, was designed to address chronic health conditions (e.g., cardiovascular disease, diabetes, and smoking) from a community perspective to estimate what it would take to implement evidence-based strategies, taking into account local contextual issues and policies related to funding health services (Burke et al, 2015). A simulation of long-term impacts of implementing clinical and community interventions in communities receiving Community Transformation Grants (CTGs) found that, assuming there was sustained funding of CTGs, up to 109,000 premature deaths could be averted and up to $8.1 billion in discounted medical costs could be produced over a 25-year period (Yarnoff et al, 2019). Modeling approaches also can address questions about how decisions might affect key populations, such as health disparity populations (McNulty et al, 2019).…”
Section: Systems Science/modeling Approachesmentioning
confidence: 99%